Health sector operational planning and budgeting processes in Kenya—"never the twain shall meet". (18th March 2015) - Tsofa, Benjamin; Molyneux, Sassy; Goodman, Catherine
Summary: Operational planning is considered an important tool for translating government policies and strategic objectives into day‐to‐day management activities. However, developing countries suffer from persistent misalignment between policy, planning and budgeting. The Medium Term Expenditure Framework (MTEF) was introduced to address this misalignment. Kenya adopted the MTEF in the early 2000s, and in 2005, the Ministry of Health adopted the Annual Operational Plan process to adapt the MTEF to the health sector. This study assessed the degree to which the health sector Annual Operational Plan process in Kenya has achieved alignment between planning and budgeting at the national level, using document reviews, participant observation and key informant interviews. We found that the Kenyan health sector was far from achieving planning and budgeting alignment. Several factors contributed to this problem including weak Ministry of Health stewardship and institutionalized separation between planning and budgeting processes; a rapidly changing planning and budgeting environment; lack of reliable data to inform target setting and poor participation by key stakeholders in the process including a top‐down approach to target setting. We conclude that alignment is unlikely to be achieved without consideration of the specific institutional contexts and the power relationships between stakeholders. In particular, there is a need for institutional integration of the planning and budgeting processes into a common cycle and framework with common reporting lines and for improved data and local‐level input to inform appropriate and realistic target setting. © 2015 The Authors. International Journal of Health Planning and Management published by John Wiley & Sons, Ltd.